2007
DOI: 10.1016/j.eurpsy.2007.02.004
|View full text |Cite
|
Sign up to set email alerts
|

Promotion of mindfulness in psychotherapists in training: Preliminary study

Abstract: This study examined whether the promotion of mindfulness in psychotherapists in training can influence the treatment results of their patients. The therapeutic course and treatment results of 196 inpatients, who were treated during a nine week period by nine psychotherapists in training, were compared: in the first phase of the study, the treatment group without (CG, historical control group, n=55), and in the second phase the treatment group with, (MFG, n=58) therapists who were currently practicing Zen medit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
30
0
3

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(33 citation statements)
references
References 16 publications
0
30
0
3
Order By: Relevance
“…Therapists feel closer to their patients, developing compassion both by becoming aware of the universality of suffering and by seeing more clearly their interconnection with others. Research in this area is just beginning (Grepmair, Mitterlehner, Loew, & Nickel, 2006;Grepmair, Mitterlehner et al, 2007).…”
Section: Practical Applications For Psychotherapymentioning
confidence: 98%
“…Therapists feel closer to their patients, developing compassion both by becoming aware of the universality of suffering and by seeing more clearly their interconnection with others. Research in this area is just beginning (Grepmair, Mitterlehner, Loew, & Nickel, 2006;Grepmair, Mitterlehner et al, 2007).…”
Section: Practical Applications For Psychotherapymentioning
confidence: 98%
“…Interestingly, studies have shown that incorporating mindbody medical stress reduction (MBMSR) or mindfulnessbased stress reduction (MBSR) into the education of health professionals and their curricula not only improves their own health status, i.e., of the student and/or therapist, but 'training the trainer' seems to have an additional and significant impact on the health outcomes of the treated patient: therapeutic success increases and the quality of care improves, just by reducing the stress in the individual therapist and by investing in his/her stress management abilities [22,23]. In an effort to foster student self-awareness and mindfulness, several medical schools have yet begun to incorporate aspects of mind-body medicine (MBM) into the curriculum [24][25][26].…”
mentioning
confidence: 99%
“…Prior research suggests that mindfulness can increase therapist presence and client treatment outcomes (Grepmair, Mitterlehner, Loew, & Nickel, 2007) and therefore should be part of counseling training. The results of this study suggest that mental health workers could benefit from training in mindfulness techniques to minimize dissociation and absorption, decrease secondary trauma symptoms (likely best identified as PTSD), and prevent burnout while increasing psychological well-being (Brown & Ryan, 2003;Davidson & McEwen, 2012;Hayes, 2004;Linehan, 1993).…”
Section: Discussionmentioning
confidence: 99%